Effect of pulse current on surface properties of aluminum oxide coating containing graphite - Md. Ghazazi, Nur Afieqah; Liza, Shahira; Ishimatsu, Jun; Mat Tahir, Noor Ayuma; Zulkifli, Nur Aszreen; Yaakob, Yazid (Wiley, 2023)
Anodizing is widely used as a surface treatment for aluminum alloy to improve its surface properties by increasing the thickness of the oxide layer. Generally, conventional anodizing by direct current (DC) produced high porosity and micro‐cracks. Utilizing pulse current (PC) as a power source and graphite particles as reinforcement for the oxide layer may solve these problems. Therefore, the present work aims to study the effect of the combination approaches on coating growth and the surface characteristics of the oxide coating. The graphite‐incorporated composite oxide coating on the AA2017‐T4 Al alloy was developed by DC and PC hard anodizing process. The surface morphology, topography, chemical composition, and surface hardness were evaluated. In PC anodizing, the growth rate of oxide layer was slower (0.59 μm/min) than DC anodizing (1.08 μm/min). The surface pores start to develop at the 30th minute compared to DC, which is the 20th minute. At 60 min, the formation of porous composite oxide coating is complete with pore dimension (width: 46.74 ± 19.96 μm and depth: 7.11 ± 2.57 μm) and thickness of 35.20 ± 8.90 μm for PC, whereas for DC pore dimension (width: 81.03 ± 21.60 μm and depth: 17.16 ± 4.31 μm) and thickness of 64.80 ± 23.69 μm. Surface roughness and hardness of composite oxide coating by PC were measured at about 1.90 ± 0.04 μm and 379.10 ± 4.37 HV, respectively. Meanwhile, the DC reveals a significant increase in roughness (4.28 ± 0.25 μm) and a decrease in hardness (302.75 ± 1.09 HV). The introduction of graphite particles with PC anodizing reduces the surface porosity, microcracks and enhances the surface hardness of oxide coating.